Genomics Gets PersonalReview of: <source>My Beautiful Genome: Exposing Our Genetic Future, One Quirk at a Time</source>; <person-group> <name name-style="western"> <surname>Frank</surname> <given-names>Lone</given-names> </name> </person-group>; ( <year>2011</year>). <publisher-name>Oneworld Publications</publisher-name>, <publisher-loc>Oxford, England</publisher-loc>. <fpage>313</fpage> pages. - Lisa Z. Scheifele (American Society for Microbiology, 2013)
Review of: My Beautiful Genome: Exposing Our Genetic Future, One Quirk at a Time; Lone Frank; (2011). Oneworld Publications, Oxford, England. 313 pages.